2023
DOI: 10.1097/ms9.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury at admission and outcomes in patients with COVID-19 disease: a prospective cohort study

Abstract: Background: The liver is one of the common extrapulmonary organs involved in the coronavirus disease 2019 (COVID-19) infection. We aimed to find the prevalence of liver injury at hospital admission and its effects on outcomes. Methods: This is a single-center prospective observational study. All consecutive patients with COVID-19 admitted during the months of May to August 2021 were included in the study. Liver injury was defined as at least 2 times ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Significantly greater risk of hepatic complications in men is usually explained by more pronounced liver steatosis and alcohol intake. Previous observations revealed that enzymatic features of liver disorder accompanying COVID-19 might predict a more severe course of the disease, poorer overall outcome and a higher rate of mortality [151][152][153][154][155]. In general, individuals affected with SARS-CoV-2 infection usually present a hepatocellular pattern of liver injury (with a threefold increase in aminotransferases above the upper limit of normal (ULN)) or a mixed one (hepatocellular pattern together with a twofold increase in ALP/GGT) [156].…”
Section: Covid-19 In Patients Without Previously Diagnosed Liver Diso...mentioning
confidence: 99%
“…Significantly greater risk of hepatic complications in men is usually explained by more pronounced liver steatosis and alcohol intake. Previous observations revealed that enzymatic features of liver disorder accompanying COVID-19 might predict a more severe course of the disease, poorer overall outcome and a higher rate of mortality [151][152][153][154][155]. In general, individuals affected with SARS-CoV-2 infection usually present a hepatocellular pattern of liver injury (with a threefold increase in aminotransferases above the upper limit of normal (ULN)) or a mixed one (hepatocellular pattern together with a twofold increase in ALP/GGT) [156].…”
Section: Covid-19 In Patients Without Previously Diagnosed Liver Diso...mentioning
confidence: 99%